2006
DOI: 10.1186/1743-422x-3-100
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Small interfering RNA targeted to stem-loop II of the 5' untranslated region effectively inhibits expression of six HCV genotypes

Abstract: Background: The antiviral action of interferon alpha targets the 5' untranslated region (UTR) used by hepatitis C virus (HCV) to translate protein by an internal ribosome entry site (IRES) mechanism. Although this sequence is highly conserved among different clinical strains, approximately half of chronically infected hepatitis C patients do not respond to interferon therapy. Therefore, development of small interfering RNA (siRNA) targeted to the 5'UTR to inhibit IRES mediated translation may represent an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 41 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…[143] Design of catalytic metallodrugs that perform RNA cleavaget owardsS LIIb can potentially inhibitthe expression of viral proteins. [144] To design ac atalytic metallodrug that targetsS LIIb of IRES RNA, at etrapeptide YrFK that selectively binds to SLIIb was used to bring the catalytic domain (CuGGH) into close proximity with the RNA substrate. [32] The designed catalytic metallodrug, CuGGHYrFK induces selectiveR NA cleavaget owards am odel oligonucleotide derived from SLIIb( 5 '-fluorescein-GGCAGAAAGCGU-CUAGCCAUGGCGUUAGUA UGCC-3').…”
Section: Rna-targeting Catalyticmetallodrugsmentioning
confidence: 99%
“…[143] Design of catalytic metallodrugs that perform RNA cleavaget owardsS LIIb can potentially inhibitthe expression of viral proteins. [144] To design ac atalytic metallodrug that targetsS LIIb of IRES RNA, at etrapeptide YrFK that selectively binds to SLIIb was used to bring the catalytic domain (CuGGH) into close proximity with the RNA substrate. [32] The designed catalytic metallodrug, CuGGHYrFK induces selectiveR NA cleavaget owards am odel oligonucleotide derived from SLIIb( 5 '-fluorescein-GGCAGAAAGCGU-CUAGCCAUGGCGUUAGUA UGCC-3').…”
Section: Rna-targeting Catalyticmetallodrugsmentioning
confidence: 99%
“…The other two (5’ UTR and NS5A) molecules only moderately knocked down the virus (< 70%). Although some studies have found that virus replication may be reduced using siRNAs directed to the 5’UTR [ 34 , 35 ] or NS5A [ 16 , 36 ], our DsiRNA molecules targeting those regions were not very efficient. Specifically, the low efficiency of the 5’UTR-targeted sequence is likely due to the highly structured nature of this site [ 37 ], which may hinder the binding of the DsiRNA molecule to its target sequence.…”
Section: Discussionmentioning
confidence: 73%
“…These reports demonstrated that siRNA targeting the HCV 5'-UTR resulted in 80%-90% inhibition of HCV. Prabhu et al [96] showed that siRNA that targets the highly conserved stem loop Ⅱ region of the HCV IRES efficiently inhibited translation and replication of infectious full-length clones of HCV 1a and 1b strains. Moreover, this siRNA effectively mediated degradation of the HCV IRES RNA and inhibited GFP expression that was controlled by the IRES sequences of six different HCV genotypes.…”
Section: Rnai Against Hcv 5'-and 3'-utr Sequencesmentioning
confidence: 99%
“…Target RNA cleavage or translation inhibition 5'-UTR and 3'-UTR [93][94][95][96][100][101][102] Protein coding regions [103][104][105][106][107][108][109] Antisense oligonucleotide Bind to complementary RNAs and suppress the access to cellular machinery, thereby inhibiting expression or function of the targeted RNAs 5'-UTR [134][135][136][137] Completion of Phase Ⅱ…”
Section: Rnaimentioning
confidence: 99%